Disruptive: Role Of Families In Educating Generation Of Century 21 - Taufiq Nur Azis; Nur Rochmat (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2020)
This study aims to examine the phenomenon that occurs in the 21st-century community. The economic needs faced by the 21st-century community are a challenge in the future. The problem concerns the loss of parental roles in providing the best primary education for children. The researcher needs to conduct a study of the loss of the part of 21st-century parents and the impact that occurred loss of a parental role in providing the best primary education. Ideally, parents should be the most crucial figure at home. As stated by Prophet Muhammad SAW that primary education is family. Then it becomes essential to figure parents in the development of their children. In this paper, we will analyze the right school for children in the 21st century, especially in the family.AbstrakPenelitian ini bertujuan untuk meneliti fenomena yang terjadi pada komunitas abad ke-21. Kebutuhan ekonomi yang dihadapi oleh komunitas abad ke-21 adalah tantangan di masa depan. Masalahnya menyangkut hilangnya peran orang tua dalam memberikan pendidikan dasar terbaik untuk anak-anak. Peneliti perlu melakukan studi tentang hilangnya bagian dari orang tua abad ke-21 dan dampak yang terjadi hilangnya peran orang tua dalam memberikan pendidikan dasar terbaik. Idealnya, orang tua harus menjadi sosok yang paling penting di rumah. Sebagaimana dinyatakan oleh Nabi Muhammad SAW bahwa pendidikan dasar adalah keluarga. Maka menjadi penting untuk menggambarkan orang tua dalam perkembangan anak-anak mereka. Dalam tulisan ini, kami akan menganalisis sekolah yang tepat untuk anak-anak di abad ke-21, terutama di keluarga.